Evaluation And Processing Of Gold At Pulai Mining, Gua Musang, Kelantan - Eang, Khy Eam (2014)
Gold mining is the important activities that create economic growth and development of the country. Effective method in gold processing is the key part in gold mining. At Pulai Mining Sdn Bhd, gold recovery is poor and it is believed that some percentage of gold lost into the tailing. This study involves characterization of samples from the area and suggests the suitable processing method to recover gold and iron with mining impacts to the environment. In this research, tailing and palong samples are studied and the following methodology is applied: laboratory sampling, mineral characterization and alluvial gold processing and then found the recovery of gold after the results of analysis and processing. Result shows that the tailing sample composed of 0.020 % of AU20 in flaky shape presented in fraction size <2.36 mm. No gold was found in palong sample (taken from middle of palong) due to its good design. Based on XRD result, tailing sample consists of hematite (FC203) 44.20 %, quartz low (Si02) 32.90 %, pyrrhotite high (FeO.lJ8SS) 13 %, pyrite (FeS2) 9 % and magnetite (Alo.IFe2.46Mgo.4204Tio.03) 0.90 %, whereas palong sample consists of quartz low (Si02) 74.60 %, hematite (Fe203) 21. 70 %, magnesium aluminum sulfide (AhMgS4) 3.20 % and pyrite (FeS2) 0.60 %.